2019
DOI: 10.1515/ger-2018-0094
|View full text |Cite
|
Sign up to set email alerts
|

Country-specific euro area government bond yield reactions to ECB’s non-standard monetary policy program announcements

Abstract: This paper employs event study methods to evaluate the effects of ECB’s non-standard monetary policy program announcements on 10-year government bond yields of 11 euro area member states. Measurable effects of announcements arise with a one-day delay meaning that government bond markets take some time to react to ECB announcements. The country-specific extent of yield reduction seems inversely related to the solvency rating of the corresponding countries. The spread between core and periphery countries reduces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 38 publications
6
15
0
Order By: Relevance
“…One interpretation of the different reactions to the ECB is that its quantitative easing policy was targeted at alleviating market crisis concerns by supporting bond yields of the peripheral Eurozone countries, rather than achieving a monetary policy objective per se, and that such support reduced safe-haven demand for bunds. That interpretation is consistent with other research that has found that ECB announcements affected markets with very long lags (often months), and those effects were not uniform in their incidence within the Eurozone, reflecting differences in country circumstances that mattered for the impact of the announcements (Mamaysky 2018, Fendel and Neugebauer 2018, Gholampour and van Wincoop 2017. From that perspective it is not surprising that the ECB is an outlier in Table 3.…”
Section: Prattle As a Measure Of Central Banks' Policy Stancesupporting
confidence: 91%
“…One interpretation of the different reactions to the ECB is that its quantitative easing policy was targeted at alleviating market crisis concerns by supporting bond yields of the peripheral Eurozone countries, rather than achieving a monetary policy objective per se, and that such support reduced safe-haven demand for bunds. That interpretation is consistent with other research that has found that ECB announcements affected markets with very long lags (often months), and those effects were not uniform in their incidence within the Eurozone, reflecting differences in country circumstances that mattered for the impact of the announcements (Mamaysky 2018, Fendel and Neugebauer 2018, Gholampour and van Wincoop 2017. From that perspective it is not surprising that the ECB is an outlier in Table 3.…”
Section: Prattle As a Measure Of Central Banks' Policy Stancesupporting
confidence: 91%
“…Ambler and Rumler (2019) conclude that the SMP and OMT announcements had the strongest negative effect on sovereign bond yields and a positive effect on expected inflation among the unconventional monetary policy announcements between July 2008 and March 2016. Fendel and Neugebauer (2020) analyze unconventional monetary policy announcements between 2007 and 2017. They differentiate countries according to their solvency and find that less solvent countries experience stronger sovereign bond yield reductions than solvent countries following announcements of non-standard monetary policies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As a consequence of this rebalancing, the prices of these other assets increase as well, thereby stimulating economic activity and raising inflation expectations. Next, there is the credit channel that describes how asset purchases lead to higher reserves at central banks for commercial banks, so that these banks can provide more loans to firms and households (Fendel and Neugebauer 2020;Altavilla et al 2015). Finally, the signaling channel, which is not easily separable from the portfolio rebalancing channel, implies lower expected monetary policy rates in the future, which instantaneously decreases long-term yields (Bauer and Rudebusch 2014;Eser and Schwaab 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations